PENGARUH PEMILIHAN METODA DEPRESIASI DAN KUALITAS AKRUAL TERHADAP KEPUTUSAN INVESTASI - AAN MARLINAH (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2015)
Depreciation method and accrual quality can affect investment decisions. Jackson 2008 and Jackson et al. 2009 showed that the selection of the depreciation method affects the investment decisions made ​​by investors. Francis et al. (2005) proved that the innate accruals quality and discretionary accruals quality affect the capital cost. Innate accruals quality has a greater effect on the capital cost compared to the effects caused by the discretionary accruals quality. This shows that the quality of financial statements will cause investors to invest and increase share returns or capital cost.